508PEfficacy and safety of anti-PD-1 antibody SHR-1210 combined with apatinib in first-line treatment for advanced lung squamous carcinoma: A phase II study. (24th November 2019) - Wang, J; Zhang, Z; Zhang, F; Song, Q; Zhang, L; Liu, Z; Ma, J; Yan, X; Wang, L; Tao, H; Zhang, S; Li, X; et al.
Abstract: Background: PD-1 antibody plus chemotherapy is a standard first-line therapy in patients with advanced lung squamous carcinoma. Previous study suggested that the combination of anti-PD-1 antibody SHR-1210 and VEGFR 2 inhibitor apatinib significantly improved antitumor effects. The aim of this study was to evaluate the efficacy and safety of SHR-1210 in combination with apatinib for advanced lung squamous carcinoma patients as a first-line treatment. Methods: Stage IIIB or IV advanced lung squamous carcinoma patients were enrolled in this open-label, single-center, single-arm phase II study. Patients received SHR-1210 (200mg q2w) and apatinib (250mg po qd) until progression or unacceptable toxicity. Treatment efficacy was assessed every 3 cycles (6 weeks). The primary end point is progression-free survival (PFS). Secondary end points are objective response rate (ORR), disease control rate (DCR) and overall survival (OS), which according to RECIST 1.1. Results: At data cut-off (July 8, 2019), 12 advanced lung squamous carcinoma patients were enrolled in the study, of which 7 patients were evaluable. Median age was 67 years, male accounts for 91.7% (11/12), clinical stage IV for 83.3% (10/12). All included patients at a median follow-up of 2.3 months (range 0.4-6.5 months). No patient achieved complete response (CR). Partial response (PR) was achieved by 6 (85.7%) patients and stable disease (SD) exhibited by 1 (14.3%) patient. The ORR and DCR were 85.7% and 100%, respectively. Grade II adverse events were observed in 4 (33.3%) patients with interstitial pneumonia (1 patient), hand-foot skin reaction (2 patients) or rash (1 patient) . One patient (1/12) died after 6 months treatment due to interstitial pneumonia and one patient was assessed by PD after 5.5 months treatment. Four patients ever suspended treatment due to interstitial pneumonia, pyelonephritis, rash or pneumothorax. Conclusions: The combination of SHR-1210 and apatinib for advanced lung squamous carcinoma patients may be a promising method as a first-line treatment. Clinical trial identification: ChiCTR1800019329 (Chinese Clinical Tiral Registry). Date of Registration: 2018-11-06. Legal entity responsible for the study: Jinliang, Wang. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.